PEMBERIAN JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PADA WANITA USIA SUBUR - Evizar, Evizar; Astriana, Astriana; Yuviska, Ike Ate; Sunarsih, Sunarsih (Universitas Malahayati Bandar Lampung, 2021)
Background High blood pressure is an increase in blood pressure in the arteries. In general, hypertension is an asymptomatic condition, in which abnormally high pressure in the arteries causes an increased risk of stroke, aneurysm, heart failure, heart attack, and heart damage. In 2018 women of childbearing age (WUS) at the Rajabasa Inpatient Health Center there were 148 people of which 46 (31.08%) had hypertension.The purpose is to know that there is an effect of giving watermelon juice on reducing blood pressure in women of childbearing age in Rajabasa Inpatient, South Lampung Regency in 2019.This type of research is quantitative, the research design is pre-experimental method with one group pretest posttest approach. The sample is 30 people, with purposive sampling technique. Data analysis with dependent T-test test.The results showed that the average blood pressure before the intervention was 150.97 mmHg/93.23 mmHg and the average blood pressure after the intervention was 132.90 mmHg/86.33 mmHg.The conclusion is that there is an effect of giving watermelon juice on reducing blood pressure in women of childbearing age in Rajabasa Inpatient, South Lampung Regency in 2019. The results of the t-test obtained p value 0.000 < (0.05).It is recommended for health workers, especially midwives, to give watermelon juice as an alternative to lower blood pressure.Keywords: Blood pressure, watermelon juice. ABSTRAK Latar Belakang Tekanan darah tinggi merupakan suatu peningkatan tekanan darah di dalam arteri. Secara umum, hipertensi merupakan suatu keadaan tanpa gejala, di mana tekanan yang abnormal tinggi di dalam arteri menyebabkan meningkatnya risiko terhadap stroke, aneurisma, gagal jantung serangan jantung, dan kerusakan jantung. Pada tahun 2018 wanita usia subur (WUS) di Puskesmas Rawat Inap Rajabasa terdapat 148 orang dimana 46 (31,08%) mengalami hipertensi.Tujuan diketahui ada Pengaruh Pemberian Jus Semangka Terhadap Penurunan Tekanan Darah Pada Wanita Usia Subur di Rawat Inap Rajabasa Kabupaten Lampung Selatan Tahun 2019.Jenis Penelitian Kuantitatif, rancangan penelitian metode pra eksperimen dengan pendekatan one group pretest posttest. Sampel sebanyak 30 orang, Dengan teknik sampling purposive sampling. Analisa data dengan uji T-test dependent.Hasil penelitian menunjukan rata-rata tekanan darah sebelum intervensi 150,97 mmHg/93,23 mmHg dan rata-rata tekanan darah setelah intervensi sebesar 132,90 mmHg/86,33 mmHg.Kesimpulan diketahui Ada Pengaruh Pemberian Jus Semangka Terhadap Penurunan Tekanan Darah Pada Wanita Usia Subur di Rawat Inap Rajabasa Kabupaten Lampung Selatan Tahun 2019. Hasil uji t didapat p value 0,000 < α (0,05).Disarankan bagi tenaga kesehatan khususnya bidan agar memberikan jus semangka sebagai salah satu alternatif menurunkan tekanan darah.Kata Kunci : Tekanan darah, jus semangka.